Artificial intelligence: A review of the philosophy of Islamic educational science - Hastuty, Ade; Maswati, Maswati; Saharuddin, Munawir; Sukri, Abdul Muqtadir; Halik, Abdul (Univeritas Papua, 2025)
The development of artificial intelligence (AI) has significantly impacted various aspects of life, including education. This study aims to explore the integration of AI within the context of Islamic education, focusing on the challenges and opportunities encountered. Utilizing a library research method, this research analyzes a range of literature discussing the relationship between AI and Islamic education, as well as the philosophical and ethical implications arising from this technological integration. The findings indicate that AI can enhance the learning experience through personalized learning, AI-based interactivity, and automated data analysis. However, challenges such as the digital divide and the potential dissemination of inaccurate content must also be addressed. This study recommends strategies to overcome these challenges, including technology literacy training for educators and the development of an integrated curriculum. With the right approach, AI has the potential to transform Islamic education, reinforcing spiritual and moral values while creating an educational system that is relevant to contemporary developments.